(E, E)-α-Farnesene as a host-induced plant volatile that attracts Apanteles taragamae (Hymenoptera: Braconidae) to host-infested cucumber plants. Issue 1 (2nd January 2018) - Nurkomar, Ihsan; Pudjianto,; Manuwoto, Syafrida; Buchori, Damayanti; Matsuyama, Shigeru; Taylor, DeMar; Kainoh, Yooichi
ABSTRACT: In tritrophic interactions between cucumber plants, the cucumber moth Diaphania indica Saunders (Lepidoptera: Crambidae) and a larval parasitoid Apanteles taragamae Viereck (Hymenoptera: Braconidae), female A. taragamae may use herbivore-induced plant volatiles (HIPVs) to locate their host. However, the specific compound or blend of chemicals attracting A. taragamae remains unknown . In this study, differences in volatiles released from uninfested, mechanically damaged and host-infested cucumber plants were examined by the headspace volatile collection method. Responses of the larval parasitoid A. taragamae to the volatile extracts were examined in a four-arm olfactometer. We also investigated the attraction of female A. taragamae to a single compound identified as an HIPV from host-infested cucumber plants. Parasitoids discriminated between the volatiles from uninfested, host-infested and mechanically damaged plants. Chemical analysis of headspace volatiles from host-infested cucumber plants showed that ( E, E ) - α-farnesene was released as a major component (73.1%). When ( E, E ) - α-farnesene was tested alone in the range of 1.7–170 ng, female parasitoids responded to 17 ng only. Therefore, tritrophic interactions between A. taragamae and D. indica appear to be partly mediated by ( E, E )-α-farnesene.